2008
DOI: 10.1088/0952-4746/28/3/r02
|View full text |Cite
|
Sign up to set email alerts
|

A review of radon measurement studies in Pakistan

Abstract: Radon is being extensively measured all over the world due to its hazardous health effects as well as for different geological applications. In this regard, considerable studies have been conducted by different research groups in Pakistan. However, these studies are scattered and need to be combined/listed somewhere for future studies of radon in Pakistan. In this article, all the studies concerning radon measurements have been reviewed. The main emphasis is on different methods used in the measurement of rado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Inhalation of radon decay products has been linked to an increased risk of lung cancer. As mentioned above, over 85% of human total annual dose, averaged over the world population, stem from natural sources, with about half of it coming from radon decay products [17][18][19][20][21][22][23]. A survey of 120 schools situated in four districts of the Punjab Province in Pakistan has been reported [24].…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of radon decay products has been linked to an increased risk of lung cancer. As mentioned above, over 85% of human total annual dose, averaged over the world population, stem from natural sources, with about half of it coming from radon decay products [17][18][19][20][21][22][23]. A survey of 120 schools situated in four districts of the Punjab Province in Pakistan has been reported [24].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, values reported for some parts of India, namely, Himachal Pradesh (45 Bq m À3 ), Assam (42 Bq m À3 ), and Meghalaya (68 Bq m À3 ) [14] are all lower than the present value. The arithmetic means reported for the North West Frontier Province in Pakistan ($65 Bq m À3 ) [17] and the cities of Rawalpindi and Lahore in Pakistan (83 and 93 Bq m À3 , respectively) [36] are also smaller than the current post-earthquake value. In the current study, for the Jhelum valley, the weighted average radon concentrations range from 81 to 509 Bq m À3 for bedrooms and 64 to 456 Bq m À3 for kitchens.…”
Section: Discussionmentioning
confidence: 69%
“…The principal source of 222 Rn inside the home is the soil surrounding the building [9]. Extensive data concerning indoor radon measurements is available in the open literature (see, for example [10][11][12][13][14][15][16][17][18][19][20] and references quoted therein). Radon measurements in soil and water of geologically fractured zones have also been reported [5,9,21].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Keeping in view the importance of the subject, like other countries of the world, 7,[10][11][12][13][14][15] radon measurement studies have also been conducted by different research groups in Pakistan. An effort was made by Faheem and Rahman 16 to compile the radon related published studies till 2007. After the publication of this article, numerous studies have been conducted and reported in the open literature.…”
Section: Introductionmentioning
confidence: 99%